Problem-based learning to develop critical thinking of elementary school students in Indonesian - Purwanto, Andrias; Efendi, Agus; Sudianto, Sudianto (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Critical thinking skills are among the foremost essential competencies in 21st-century education, playing a crucial role in effective decision-making and systematic problem-solving. This study aimed to analyze the impact of implementing Problem-Based Learning (PBL) to enhance critical thinking skills of elementary school students in Indonesian language learning. The method employed is a systematic literature review guided by the PRISMA protocol, encompassing the identification, screening, and analysis of relevant studies. The findings revealed that PBL significantly improves students’ abilities in analysis, logical reasoning, evaluation, and argument construction. Beyond cognitive skills, PBL also enhances social skills such as communication and collaboration within the learning process. Challenges faced in PBL implementation include limited time, teacher preparedness, and curriculum demands. Overall, PBL proves to be an effective and relevant instructional approach for cultivating critical thinking skills, particularly in Indonesian language education at the elementary level. These findings support the adoption of PBL in teaching practices to create more meaningful, student-centered learning experiences.